Remote and Proximal Delivery of The Laboratory Component of Electrical and Energy Systems Course - Stamen Gadzhanov; Andrew Nafalski; Aji Prasetya Wibawa (Jurnal Pendidikan Sains, 2017)
Abstract: This paper describes the practical activities of Electrical Energy Systems (EES) course at University of South Australia (UniSA). The practical subject is Laboratory Component (LC). It is a compulsory subject for first-year students of bachelor of the engineering program. Students may do practically in conventional laboratories or by using Internet-based remote laboratory (RL). An experiment was conducted to explore the students’ preference for practical approaches. Most students prefer the RL schedule flexibility while the others like to do real component wiring in an electrical laboratory. The combination between proximal and remote laboratories may become the best approach to delivering the LC practical.Key Words: real laboratory, remote laboratory, laboratory componentAbstrak: Tulisan ini menjelaskan kegiatan praktis pada matakuliah Electrical Energy Systems (EES) di University of South Australia (UniSA). Subjek praktis dalam penelitian ini adalah Laboratory Component (LC). Sebagai matakuliah wajib untuk mahasiswa tahun pertama dari sarjana program rekayasa. Siswa diharapkan dapat melakukan praktek di laboratorium konvensional atau dengan menggunakan remote laboratorium berbasis internet (RL). Penelitian dilakukan untuk mengeksplorasi preferensi siswa pada pendekatan praktis. Kebanyakan siswa lebih suka fleksibilitas jadwal RL sementara yang lain ingin melakukan real component wiring di laboratorium listrik. Kombinasi antara laboratorium proksimal dan terpencil mungkin menjadi pendekatan terbaik untuk memberikan LC praktis.Kata kunci: laboratorium nyata, laboratorium terpencil, komponen laboratorium